Purchasing power parity in the long run and structural breaks: Evidence from real sterling exchange rates - Parkes, Andrew L.H.; Savvides, Andreas (My University, 1999)
The paper contributes to the growing evidence in favour of mean reversion in real exchange rates of industrial countries. The sequential regression model is used to search for endogenous structural breaks in long-term annual sterling exchange rates for the G-7. Any structural breaks thus detected are introduced into a system of univariate autoregressions of the real exchange rate estimated jointly via restricted GLS. Multivariate unit root tests reject the null hypothesis decisively. Our evidence, however, shows that reversion of long-term sterling exchange rates is towards a mean that (for some exchange rates) experiences a structural shift at an endogenously determined date.